Representasi Nilai Pendidikan Karakter dalam Novel 00,00 Karya Ameylia Falensia - Mutia Sari Devi; Siti Aisyah (Yayasan Pendidikan Penelitian Pengabdian Algero, 2024)
Literary works, especially novels, are new prose that tells the story of life journey of the main actor which contains conflict which really attracts the reader's interest so that the reader can understand the message that conveyed by the author. Researchers used the novel 00.00 by Amylia Falensia which tells the story of the life of a girl who always faces tragic sadness and conflict. In this research, the author aims to analyze the positive side, namely the value of character education in the novel 00.00 by Ameylia Falensia. The approach taken in this research is a qualitative approach. Meanwhile, the method used for document analysis is reading the novel repeatedly and marking quotations from the novel 00.00 by Amylia Falensia. The analysis of character education values ​​found are: 1) Religious, 2) Honest, 3) Tolerant, 4) Independent, 5) Democratic, 6) Love peace, 7) Friendly, 8) Social care, 9) Hard work, 10) Responsibility, 11) Creative and 12) Loves reading